Trends and Applications in Knowledge Discovery and Data Mining : PAKDD 2015 Workshops: BigPMA, VLSP, QIMIE, DAEBH, Ho Chi Minh City, Vietnam, May 19-21, 2015. Revised Selected Papers - Li, Xiao-Li.; Cao, Tru.; Lim, Ee-Peng.; Zhou, Zhi-Hua.; Ho, Tu-Bao.; Cheung, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings at PAKDD Workshops 2015, held in conjunction with PAKDD, the 19th Pacific-Asia Conference on Knowledge Discovery and Data Mining in Ho Chi Minh City, Vietnam, in May 2015. The 23 revised papers presented were carefully reviewed and selected from 57 submissions. The workshops affiliated with PAKDD 2015 include: Pattern Mining and Application of Big Data (BigPMA), Quality Issues, Measures of Interestingness and Evaluation of data mining models (QIMIE), Data Analytics for Evidence-based Healthcare (DAEBH), Vietnamese Language and Speech Processing (VLSP).
ProbitUCB: A Novel Method for Review Ranking. From Cluster-based Outlier Detection to Time Series Discord Discovery -- Web site audience segmentation using hybrid alignment techniques -- Mining Massive-Scale Spatiotemporal Trajectories in Parallel: A Survey -- Manifold Regularized Symmetric Joint Link Model for Overlapping Community Detection -- High Dimensional Explicit Feature Biased Matrix Factorization Recommendation -- A Simhash-based Generalized Framework for Citation Matching in MapReduce -- A Cloud Based Diabetes Lifestyle Management System -- Construction of a prediction model for nephropathy among obese patients using genetic and clinical features -- A Research of Applying Association Rules and Decision Tree to Endometriosis -- A Dynamic Feature Selection Based LDA Approach to Baseball Pitch Prediction -- A Study of Interestingness Measures for Associative Classification on Imbalanced Data -- Evaluation of Community Mining Algorithms in the Presence of Attributes -- Leveraging the Common Cause of Errors for Constraint-based Data Cleansing Analyzing User Behaviors Based on Temporal Patterns of Sequential Pattern Evaluation Indices on Twitter -- Model Selection of Symbolic Regression to Improve the Accuracy of PM 2.5 Concentration Prediction -- Internal Clustering Evaluation of Data Streams -- Feature maximization based clustering quality evaluation: a promising approach -- Integrating Content Centric Networking and Web Content Mining: A Future Efficient Internet Architecture for Healthcare -- Citation enrichment improves deduplication of primary evidence -- Learning Entry Profiles of Children with Autism from Multivariate Treatment Information using Restricted Boltzmann Machines -- Fast Dependency Parsing using Distributed Word Representations -- Modeling Vietnamese speech prosody: A step-by-step approach towards an expressive speech synthesis system. .
Keywords: Data mining; Artificial intelligence; Medical records -- Data processing; Information storage and retrieva; Computer science; Data Mining and Knowledge Discovery; Artificial Intelligence; Health Informatics; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Computation by Abstract Devices